Efektivitas Metode Brent dalam Penyelesaian Masalah Break Even Point Menggunakan Pemrograman Pascal - Sujaya, Ketut Ary; Sudi Prayitno; Nani Kurniati; Nyoman Sridana (Mandalika Mathematics and Educations Journal, 2024)
The non-linear mathematical model of the break even point (BEP) problem is difficult to solve analytically to obtain an exact solution, so the alternative is to solve it numerically. This research aims to solve the BEP problem and measure the effectiveness of Brent's method compared to other solution methods based on error and number of iterations. This research is an applied type whose implementation procedures include preparation, implementation, program testing, program revision, analysis, and conclusion. The errors of Brent’s, secant, false position, and bisection methods in solving the BEP problem are 0.00118; 0.00893; 0.64485; and 0.89119, respectively. While the number of iterations from several checks are 52, 53, 91, and 101, respectively. Therefore, it can be concluded that the Brent’s method is more effective than the other three methods.